"How to Do It": Hybrid Stent Placement for Pulmonary Vein Stenosis. (April 2015) - Shell, Kathryn J.; Ebeid, Makram R.; Salazar, Jorge D.; Dodge-Khatami, Ali; Batlivala, Sarosh P.
Pulmonary vein stenosis (PVS) is often progressive and severe. Surgical and percutaneous angioplasty are acutely successful; however, restenosis is common and many patients require multiple reinterventions. We perform intraoperative "hybrid" stent placement to deliver larger, stronger stents. Hybrid stent placement is well described for pulmonary arterial stenosis (PAS). The PAS data demonstrate that smaller stents are associated with rapid in-stent restenosis. Data from PVS in adults demonstrate superior outcomes with larger stents. Hybrid stent placement requires a strong collaborative effort between congenital heart surgeons and interventional cardiologists.